Fragmented authoritarianism, selective control and the rise of entrepreneurs - Xu, X (2011)
The dynamics of state-NGO relations in China is viewed through the analytical lens of 'fragmented authoritarianism'. It is suggested that the fragmented political structure that results in interagency bargaining and problems of coordination is a main reason for the inconsistency in state behaviour. State actors form diverse and sometimes conflicting strategies towards social organizations based on their own interests as well as an NGO issue-framing, with service-based NGO receiving more favourable treatment and rights-base groups facing escalated pressure, a model summarized as 'selective control'. The ambiguity in the regulations and administration of NGOs gives the state maximum flexibility in handling NGOs. The leaders of the more persistent service-based and rights-based NGOs often act as effective social entrepreneurs and policy entrepreneurs respectively. They are joined by private entrepreneurs, who are becoming as a major source of funding for NGOs through private foundations. With similar preference to the state, they act as a proxy to the state with selective funding that favours serviced-based NGOs, which results in a more treacherous conditions and further stagnation of resources for rights-based NGOs.